$S$-colocalization and Adams cocompletion - Choudhury, Snigdha Bharati; Behera, A. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512A relationship between the $S$-colocalization of an object and the  Adams cocompletion of the same object in a complete small $\mathscr{U}$-category ($\mathscr{U}$ is a fixed Grothendieck universe)   is established, together with a specific set of morphisms $S.$